Kebijakan Hukum Pidana dalam Upaya Penanggulangan Tindak Pidana Lingkungan Hidup - Reza Pahlefi Fajrin (Indragiri Law Review, 2025)
This research aims to analyse the effectiveness of criminal law policy in tackling environmental crimes in Indonesia, identify obstacles in law enforcement, and provide recommendations for improvement. This research uses a normative juridical method, with a descriptive-analytical approach that utilises analysis of laws and regulations, literature studies, and evaluation of environmental pollution cases. The data was analysed qualitatively to assess the effectiveness of the application of criminal sanctions under Law No. 32/2009 on Environmental Protection and Management (UUPPLH). The research findings show that although UUPPLH regulates significant criminal sanctions, its effectiveness is still limited by factors such as low capacity of law enforcers, weak coordination between institutions, and minimal public awareness. Criminal law enforcement often faces technical obstacles, including a lack of trained human resources and complex evidentiary processes, especially against large corporations. In addition, administrative sanctions such as revocation of business licences are often considered more effective than criminal sanctions. The conclusion of this study is that criminal law, although important, has not been fully effective in providing a deterrent effect for perpetrators of environmental crimes. Strengthening regulations, increasing the capacity of law enforcement officers, and synergy between preventive and repressive approaches are needed to optimise criminal law policies in environmental protection.